DNA methylation of GJA1, BMP2 and BMP4 in a human cementoblast cell line induced by lipopolysaccharide. (22nd February 2020) - Kobayashi, F.; Uehara, O.; Ito, C.; Furusawa, M.; Abiko, Y.; Muramatsu, T.
Abstract: Aim: To examine DNA methylation of GJA1, BMP2 and BMP4 in human cementoblasts (HCEM) induced by lipopolysaccharide (LPS). Methodology: HCEM were cultured in osteoinduction medium. After 24 h, Escherichia coli LPS (1 μg/mL) was added to the medium, which was changed every 2–3 days. Untreated samples were used as controls. Messenger RNA was extracted after 4 weeks, and quantitative real‐time polymerase chain reaction (qRT‐PCR) for GJA1, BMP2, BMP4 and DNMT1 was performed. Genomic DNA was extracted after 4 weeks, and quantitative methylation‐specific polymerase chain reaction was carried out for GJA1, BMP2 and BMP4 . To detect mineralization, alizarin red and alkaline phosphatase staining were performed. The cells were also treated with the DNA methyltransferase inhibitor 5‐Aza‐2'‐deoxycytidine (5Aza) and examined. The significance of differences amongst groups was assessed using a two‐way analysis of variance (ANOVA) followed by Bonferroni's multiple comparison test with P  < 0.05 being significant. Results: Decreased expression of mRNA was seen in GJA1, BMP2 and BMP4 after 4 weeks ( P  < 0.05). DNA hypermethylation was detected in GJA1, BMP2 and BMP4 ( P  < 0.05). Alizarin red staining and alkaline phosphatase staining revealed decreased mineralization levels in HCEM stimulated with LPS. 5Aza abolished the effects of DNA methylation in HCEM stimulated with LPS. Conclusions: These results suggest that long‐term LPS stimulation induces DNA methylation of GJA1, BMP2 and BMP4 in HCEM.